CHIP, a carboxy terminus HSP-70 interacting protein, prevents cell death induced by endoplasmic reticulum stress in the central nervous system - Cabral Miranda, Felipe; Adão-Novaes, Juliana; Hauswirth, William W.; Linden, Rafael; Petrs-Silva, Hilda; Chiarini, Luciana B. (Frontiers in Cellular Neuroscience, 2015)
Endoplasmic reticulum (ER) stress and protein misfolding are associated with various neurodegenerative diseases. ER stress activates unfolded protein response (UPR), an adaptative response. However, severe ER stress can induce cell death. Here we show that the E3 ubiquitin ligase and co-chaperone Carboxyl Terminus HSP70/90 Interacting Protein (CHIP) prevents neuron death in the hippocampus induced by severe ER stress. Organotypic hippocampal slice cultures (OHSCs) were exposed to Tunicamycin, a pharmacological ER stress inducer, to trigger cell death. Overexpression of CHIP was achieved with a recombinant adeno-associated viral vector (rAAV) and significantly diminished ER stress-induced cell death, as shown by analysis of propidium iodide (PI) uptake, condensed chromatin, TUNEL and cleaved caspase 3 in the CA1 region of OHSCs. In addition, overexpression of CHIP prevented upregulation of both CHOP and p53 both pro-apoptotic pathways induced by ER stress. We also detected an attenuation of eIF2a phosphorylation promoted by ER stress. However, CHIP did not prevent upregulation of BiP/GRP78 induced by UPR. These data indicate that overexpression of CHIP attenuates ER-stress death response while maintain ER stress adaptative response in the central nervous system. These results indicate a neuroprotective role for CHIP upon UPR signaling. CHIP emerge as a candidate for clinical intervention in neurodegenerative diseases associated with ER stress.